Group Counseling Using Assertive Training Techniques with Virtual Reality Based on Artificial Intelligence Video to Improve Assertiveness in Students with Nice Girl Syndrome: A Quasi-Experimental Study - Ahmad Wahid; Yarmis Syukur; Afdal; Puji Gusri Handayani (Postgraduate, University of Mataram, 2026)
The nice girl syndrome is a phenomenon that has a negative impact on individuals' lives, causing teenage girls to have poor interpersonal relationships. One way to overcome this problem is to practice assertiveness. This study aims to test the effectiveness of group counseling using assertive training techniques with virtual reality based on artificial intelligence video to improve the assertiveness of students with nice girl syndrome. This research uses a quasi-experimental method with a non-equivalent control group design. The sample consists of 20 female students selected using purposive sampling. The instruments used in this study were an assertive behavior scale that had been tested for validity and reliability, and a nice girl syndrome scale developed by Beverly Engel. Data analysis was performed using the Wilcoxon formula (Signed Rank Test), Mann-Whitney U, and N-gain score test. The results of the study showed that the application of group counseling services using assertive training techniques, combined with virtual reality based on artificial intelligence video in the experimental group, can improve the assertive behavior of students with Nice Girl Syndrome more effectively. This can be seen from the two tests conducted, namely using the Mann-Whitney U formula and the N-gain Score test. The results of this study provide new directions and effective innovations in the implementation of group counseling in the digital technology era, and further development is needed for a wider population.